Khư̄n khwāmkhēmkhǣng hai khrō̜pkhrūa khon Nān (Sūn Kānrīanrū phư̄a Khrō̜pkhrūa Khēmkhǣng Čhangwat Nān, Mūnnithi Hak Mư̄ang Nān, 2009)
Community participation and voluntary activities for having social issues-free and for building strength and happiness to the families of people in Nan province, Northern Thailand.